Effectiveness of African Wattle Tree (Peltophorum africanum) Biochar in Removing Carmoisine Dye from Wastewater - Burukai, Christine; Nyoni, Bothwell; Nyama, Dorcas; Mpofu, Clever; Hlabano-Moyo, Bongibethu; Yalala, Bongani; Mnyango, Jabulani I.; Hlangothi, Shanganyane P. (Asian Journal of Chemistry, 2025)
In this work, the use of biochar synthesized from the African wattle tree (Peltophorum africanum) bark as an adsorbent for the removal of carmoisine, a common red azo dye from a simulated effluent, is investigated. The study focuses on the effect of adsorbent synthesis conditions, particularly the carbonization temperature, then, the adsorption process conditions and finally, analyzing the relevant isotherms, kinetics and mechanisms. It was revealed that the point of zero charge for the activated biochar prepared at 500, 600 and 700 ºC were 6.6, 6.5, and 6.3 respectively, indicating that the surface charge of the adsorbent became more positive as temperature was increased. Consequently, all adsorbent samples displayed a decrease in removal efficiency when the pH of the solution increased. Adsorption experiments revealed that the process best fits the Langmuir isotherm model with monolayer adsorption capacities of 49.8, 56.1 and 63.8 mg g–1 for activated biochars prepared at 500, 600, and 700 ºC, respectively. Kinetics studies further reveal that the adsorption process generally follows pseudo-second-order kinetics with k2 values in the range of 0.01–0.1 min–1. The most probable adsorption mechanisms involve hydrogen bonding and electrostatic interactions due to the presence of carbon-oxygen and carbon-nitrogen functional groups.